Development of Children’s Sleep Habit Questionnaire Thai version. - Disayawanwat , P.; Pityaratstian , N. (Chulalongkorn Medical Journal, 2023)
Background : Adequate duration and quality of sleep are increasingly recognized as important determinants of child and adolescent health. In adequate sleep may impact daytime cognitive functions, academic performance, behaviors, emotional regulation, risk of obesity and the risk of accidental falls. Children’s Sleep Habit Questionnaire (CSHQ) is designed to screen for most common sleep problems in children. CSHQ consists of 33 items for scoring. Objective : To develop a Thai Version of Children’s Sleep Habit Questionnaire by translating and retranslating the English version of CSHQ and to examine the reliability, content validity, a Thai version in 4 - 10 years old children. Design : Descriptive study. Setting : King Chulalongkorn Memorial Hospital, Bangkok and Samakomsatreethai School, Bangkok. Method : The questionnaire was adapted to Thai language according to international guidelines. The content validity is measured by three child psychiatrists. The questionnaire was administered to the parents of 60 children aged 4 – 10 years. Result : The Thai Version of CSHQ has the internal consistency of 0.83 (Cronbach’s α) for the total scale and ranges from 0.392 to 0.776 for the subscales. Cronbach’s α are 0.47 (bedtime resistance), 0.49 (sleep duration), 0.615 (sleep anxiety), 0.776 (night wakenings), 0.736 (parasomnias), 0.392 (sleep disordered breathing) and 0.78 (daytime sleepiness) Conclusion : The Thai version of the CSHQ demonstrates satisfactory reliability and validity in community and clinical populations. This is the first study to demonstrate psychometric properties of the CSHQ. Further studies of other psychometric properties are needed.